ASSESSMENT OF RADIOLOGICAL IMPACTS FROM POSTULATED ACCIDENT CONDITIONS OF HTGR: A CASE STUDY IN SERPONG NUCLEAR AREA - Muhammad Budi Setiawan; Ihda Husnayani; Heni Susiati (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
High Temperature Gas-cooled Reactor (HTGR) design has an improved safety which depends on its TRISO coated fuel particles that are considered not to be damaged even in accident condition. However, the radiological impacts from accident condition in HTGR is still important to be assessed. This research is aimed to perform radiological impacts assessment of two postulated accidents of HTGR, which are depressurization and water ingress accident. As a case study, a 10-MWTh pebble-bed HTGR design named Reaktor Daya Eksperimental with the planned site located in Serpong Nuclear Area was chosen. The source terms from the accident conditions were estimated using mechanistic source term model and the dose consequences were calculated using PC-COSYMA. The input data for PC COSYMA, which are meteorological, population distribution, agricultural and local farm data, were compiled based on the site data of Serpong Nuclear Area. The radiological impacts were assessed based on individual and collective doses. The results showed that the highest dose will be received by the community within a radius of 250 m to the south from the reactor. It was also found that these accidents only cause minor radiological impacts which do not meet the criteria for any countermeasures (iodine thyroid blocking, sheltering, evacuation, food ban, decontamination, and relocation).